FORMULATION AND EVALUATION OF AN INNOVATIVE ANTI - WRINKLE CREAM ENRICHED WITH BIO-RETINOL - Akshay V. Rasal; Kedar Patila
This research analyses the productivity of a bio-retinol anti-aging skin cream, highlighting probiotics and retinol. The study expands upon their roles in increasing skin health structure and challenging aging effects. Key matrix materials, comprising rosehip oil, safflower oil, bifida ferment lysate, CoQ enzyme, hyaluronic acid and fractionated coconut oil, provide to the cream$1 (Bs formulation. Results reveal a balanced pH (5.45 - 5.81), homogeneity, and perfect spreadability. The cream expresses positive outcomes, presenting a promising solution for improved skin elasticity and extensive anti-aging benefits.s